ANALISIS MATERI SEJARAH LOKAL DALAM MENANAMKAN SIKAP NASIONALISME PESERTA DIDIK SMA NEGERI 1 PONTIANAK - Delta, Delta; Noor, Agus Sastrawan; Firmansyah, Andang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to obtain clear and accurate information about the learning material of local history, in instilling nationalism in students of class XI Pontianak 1 State High School. The research method used is descriptive qualitative research method in the form of case study research. The source of this research data is the history subject teacher, the 11th grade student, and the deputy head of the curriculum in the Pontianak City State Senior High School 1. The data is history learning which contains the existence of local historical material, in instilling nationalism in students and the results of interviews and observations, as well as documentation. Based on the results of the study showed that the teacher has not included local historical material in planning, but in the learning process the teacher has delivered local history material this is evidenced by the existence of daily test questions that contain the existence of local historical material. Local history material in instilling nationalism in students especially class XI in Pontianak 1 State High School is already good, which is shown from the learning and evaluation process which has included local history material so that there is a change in attitude towards students related to their nationalism attitude.But there are still some that have not been optimally seen from planning that have not included the existence of local historical material. Keywords: Local History Material, Nationalism, Students.